Inner-shell soft x-ray lasers driven by optical field ionization - Hooker, S (IEEE, 2000)
Presented is a novel approach for driving short-wavelength lasers, with good prospects for scaling to shorter wavelengths. Present investigations include analysis of extensions to other transitions such as the 3s → 3p and 3p → 3d hole transitions in Ni-like ions following monopole excitation of 3s and 3p holes in OFI plasmas. The results of those calculations are presented.